Association between dietary patterns and glycemic control in type II diabetes mellitus patients - Ye Qiang; Xingchen Lu; Yuchao Zhang (Atención Primaria)
Objective: To assess the association between dietary patterns and glycemic control among patients with type II diabetes mellitus (T2DM). Design: A cross-sectional study. Site: The 2015–2018 National Health and Nutrition Examination Survey (NHANES). Participants: A total of 1646 T2DM patients were included, of whom 854 were hyperglycemia. Methods: Main dietary patterns were identified using the sparse principal components analysis (SPCA). Logistic regression analysis was applied to investigate the association between each dietary pattern and the risk of hyperglycemia with odds ratios (OR) and 95% confidence intervals (CI). SPCA analysis yielded five significant principal components (PC), which represented five main dietary patterns. Results: PC1, characterized by a high intake of sweets, red meat and processed meat, was associated with higher odds of hyperglycemia in patients who underwent hyperglycemic drug or insulin treatments (OR: 1.71, 95% CI: 1.10–2.64). PC5, characterized by high in red meat, while low in coffee, sweets, and high-fat dairy consumption. The relationship between the PC5 and hyperglycemia was marginal significance (OR: 0.63, 95% CI: 0.38–1.02). PC2 was characterized by a high consumption of green vegetables, other vegetables, and whole grains, and low intake of potatoes and processed meat. In patients with the hyperglycemic drug and insulin free, higher PC2 levels were related to lower odds of hyperglycemia (OR: 0.45, 95% CI: 0.21–0.96). Conclusions: High intake of sweets, red meat, and processed meat might be detrimental to glycemic control in patients with drug-treated T2DM. High in red meat, while low in coffee, sweets, and high-fat dairy consumption may be beneficial to glycemic control. In addition, high consumption of green vegetables, other vegetables, and whole grains, and low intake of potatoes and processed meat may be good for glycemic control in patients without drug-treated T2DM. Resumen: Objetivo: Evaluar la relación entre el patrón dietético y el control de la glucosa en sangre en los pacientes con diabetes mellitus tipo II (DM2). Diseño: Estudio transversal. Sitio: Encuesta Nacional de Salud y Nutrición 2015-2018 (NHANES). Participantes: Un total de 1.646 pacientes con DM2 fueron incluidos, de los cuales 854 fueron pacientes con hiperglucemia. Método: Se utilizó el método de análisis de componentes principales escasos (SPCA) para determinar el modo dietético principal. Se aplicó un análisis de regresión logística para estudiar la relación entre cada patrón dietético y el riesgo de hiperglucemia con una relación de relación (OR) y un intervalo de confianza (IC) del 95%. El análisis del SPCA ha obtenido 5 componentes principales importantes (PC), que representan los 5 principales patrones alimenticios. Resultados: El PC1 se caracteriza por una alta ingesta de dulces, carnes rojas y procesadas, y se asocia con una mayor probabilidad de hiperglucemia en los pacientes tratados con medicamentos hiperglucémicos o insulina (OR: 171; IC 95%: 1,10-2,64). El PC5, que se caracteriza por un alto contenido de carne roja, mientras que el consumo de café, dulces y productos lácteos ricos en grasas es bajo. La relación entre PC5 y la hiperglucemia fue marginal (OR: 0,63; IC 95%: 0,38-1,02). El PC2 se caracteriza por un alto consumo de verduras verdes, otras verduras y cereales integrales, y una baja ingesta de patatas y carne procesada. Los niveles más altos de PC2 se asociaron con una menor probabilidad de hiperglucemia (OR: 4,45; IC 95%: 0,21-0,96) en los pacientes que tomaban medicamentos hiperglucémicos y no tenían insulina. Conclusión: La alta ingesta de dulces, carnes rojas y procesadas puede no ser propicia para el control de la glucosa en sangre en los pacientes con DM2 tratados con medicamentos. La ingesta de carne roja alta, café bajo, dulces y productos lácteos ricos en grasas puede favorecer el control de la glucosa en sangre. Además, el alto consumo de verduras verdes, otras verduras y cereales integrales, la baja ingesta de patatas y de carne procesada pueden favorecer el control de la glucosa en sangre en los pacientes con DM2 sin tratamiento farmacológico.